Developing Cultural Character Through the Habit of Using Krama Language in Surakarta City Elementary Schools - Susiyani, Retno; Prayitno, Harun Joko; Rahmawati, Fitri Puji; Sutama, S; Rahmawati, Laili Etika (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this study is to explore teachers' efforts in developing cultured character through the habituation of Javanese krama language. Methodology: This research is a qualitative descriptive method research, the subjects of the research were the principal, grade V teachers, and grade V students totaling 28 people, consisting of 13 male students and 15 female students. The data collection techniques for this research were participatory observation, in-depth interviews, and document analysis. The data analysis method used the steps of data collection, data reduction, data presentation, verification and drawing conclusions. Results: The results of students' krama language skills are divided into two categories, from 28 students, 65% of students were in the good category and 35% of students were in the poor category. Applications/Originality/Value: Teachers' efforts in developing cultured characters through the habit of using krama language are carried out with two solutions. First, utilizing multimedia learning media (Si Bawa) as a form of teacher innovation in introducing krama language to students. Second, the habit of communicating in krama language every Wednesday, as a stimulus for students to get used to communicating in krama language and strengthening cultured characters in everyday life.